Development of Disaster Education Tourism Model at Rembat Beach Tourist Attraction of Indramayu - Lailul Febriyanti; Tedi Abadi Yanto; Yedo Kurniawan (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2023)
The development of the tourism sector is starting to return with various new concepts to attract tourists, including the development of Educational Tourism or Edu-tourism. The result of this edu-tourism area is inseparable from the background of the tourist attraction area, which is considered to have characteristics and selling points that can attract tourists. No exception was made at Rembat Beach, Juntinyuat Village, Indramayu Regency. This research was conducted using a descriptive method with a qualitative approach to describe the development of a disaster education tourism model with market penetration, product development, and market development. In addition, product development and market development were also carried out, which increased visits by 12% and provided additional village income with an average of Rp1,200,000/month. The last effort related to product diversification still requires a study of the success of abrasion-based edu-tourism development.